Pelatihan Penulisan Naskah Ilmiah Jurnal Investigasi Volume 3 Nomor 2 September-Februari 2023 Bagi Guru-Guru se Kota Tangerang Selatan - Gatot Kusjono; Suprianto Suprianto; Syamruddin Syamruddin (Indonesian Journal of Society Engagement, 2022)
Community service activities Training for Scientific Manuscript Writing of Investigative Journals Volume 3 Number 2 September-February 2023 for Teachers throughout South Tangerang City aims to assist elementary / junior high school / junior high school / high school / vocational school teachers in South Tangerang City in writing scientific manuscripts that will be published in ISSN journals. The training method is carried out using the method of assistance, discussion, workshops and technical guidance (bimtek) for writing scientific manuscripts in accordance with journal manuscript standards. The results of the training were obtained as many as 8 elementary school teacher manuscripts (57%), 4 junior high school teacher manuscripts (29%), 1 high school / vocational teacher manuscript (7%), and the P& K 1 manuscript (7%) published in the journal INVESTIGATION Volume 3 Number 2 September 2 September 2023. The publication of teacher scientific manuscripts in the journal INVESTIGATION is certainly very helpful for teachers in fulfilling the obligation to journal their scientific manuscripts, so that they are not constrained in class or position promotion.